Manifestações do sono e da deglutição em indivíduos com doença pulmonar obstrutiva crônica - Silva, Gabriele dos Anjos Palagi da (2021)
Introduction: Swallowing is the act of taking food from the oral cavity to the stomach in a safe way, aiming to protect the airway and maintain the individual's nutritional status. When an abnormality, anatomical or functional, appears at any stage of the swallowing process, the result is the installation of dysphagia. In patients with Chronic Obstructive Pulmonary Disease (COPD), abnormalities in respiratory and ventilatory patterns can interfere with the coordination between swallowing and breathing, leading to dysphagia. In addition, reports indicate that COPD is associated with sleep disorders and excessive daytime sleepiness. Obstructive Sleep Apnea Syndrome (OSAS) and COPD are common clinical conditions, and a large number of COPD patients are expected to present with SOAS. Objective: To characterize and relate the manifestations of sleep and swallowing in individuals with COPD. Methods: This is a cross-sectional study, carried out in the Pulmonary Rehabilitation unit of a University Hospital. The sample includes 37 patients with COPD, of both genders, in outpatient follow-up. The patients were evaluated regarding aspects of body composition, peak expiratory flow, perception of dyspnea (Modified Medical Research Council - mMRC), impact of the disease on health status (COPD Assessment Test - CAT), excessive daytime sleepiness (Scale of Epworth sleepiness - ESS), risk of sleep apnea (Berlin Clinical Questionnaire), modified Mallampati index and symptoms indicative of dysphagia (Questionnaire for Dysphagia Screening - QDS). Data were analyzed using multivariate analysis, the level of significance was set at 5%, with a 95% confidence interval. Results: In this sample consisting of individuals with moderate to severe COPD, 83% of them reported symptoms of swallowing dysfunction assessed by the QDS and 62.2% were at risk for sleep apnea. The CAT, Epworth and Berlin indices predicted 32% of the risk for dysphagia. Conclusion: Among individuals, the high frequency of risk for dysphagia present in 31 (83.8%) of the subjects can be observed. Similarly, the risk for sleep apnea was present in 23 (62.2%) patients in the sample. Furthermore, abnormal sleepiness was observed in 14 (37.8%) of the patients. The impact of the disease on health status, daytime sleepiness scores and risk of sleep apnea were the best predictors of dysphagia risk for COPD among those surveyed. In this sense, it is proposed that assessments of health status, drowsiness and QDS be included in the assessment routine of patients with COPD.